Resting state brain network functional connectivity is not associated with inflammatory markers and blood cell counts in older adults. Issue 7 (July 2021) - Lichtner, Gregor; Zacharias, Norman; Spies, Claudia D.; Feinkohl, Insa; Winterer, Georg; Pischon, Tobias; von Dincklage, Falk
Highlights: Systemic inflammation and monocyte counts have been previously associated with changes in functional connectivity studies. We analyzed a longitudinal dataset of older adults and found no such associations, contrasting previous studies. Longitudinal studies as performed here provide a way to validate results, preventing inflated false positives rates. Abstract: Objective: Systemic inflammation and monocyte counts have previously been associated with changes in resting state functional connectivity (rsFC) in cross-sectional neuroimaging studies. We therefore investigated this association in a longitudinal study of older patients. Methods: We performed a secondary analysis of longitudinal data from older patients who underwent functional magnet resonance imaging (fMRI) scans before and 3 months after elective surgery. Additionally, serum levels of C-reactive protein and Interleukin-6 as markers of inflammation and leukocyte, lymphocyte and monocyte counts were determined. Correlations between these markers and pre- or postoperative rsFC between regions previously associated with inflammatory markers were investigated using general linear regression models. Results: We found no significant correlations between inflammatory markers or blood cell counts and mean connectivity within four resting state networks (RSNs), neither preoperatively nor postoperatively. Significant inter-region rsFC was found within these RSNs between a few regions either pre- or postoperatively, but no inter-region connections were consistently observed in both pre- and postoperative fMRI scans. Conclusions: Inflammatory markers and monocyte counts were not associated with rsFC in our study, contrasting previous results. Significance: Multiple measurements in the same individuals, as performed here, provide a way to reduce the high risk of false positive results in fMRI studies. Trial Registration: Clinicaltrials.gov (registration number NCT02265263).